(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Contemporary fiction is acted upon concerning gender, concerning the type of narrative viewpoints and how a narrative is narrated and the experience is described through the characters. The paper is an exploration of how gendered views impact on the construction of narratives; in this case, the male and female gaze, first and third person perspectives, and how gender and race, class, and sexuality intersect. The paper determines the relationship between gender and storytelling and character development in modern fiction, which reflects the social and cultural implications and meanings in it.